Exploring new dimensions in cadaveric decomposition odour analysis. Issue 6 (3rd March 2015) - Stefanuto, P.-H.; Perrault, K. A.; Lloyd, R. M.; Stuart, B.; Rai, T.; Forbes, S. L.; Focant, J.-F.
Abstract : This study demonstrates the first documented use of comprehensive two-dimensional gas chromatography – high-resolution time-of-flight mass spectrometry (GC×GC-HRTOFMS) for volatile organic compound analysis in the forensic sciences. Abstract : This study demonstrates the first documented use of comprehensive two-dimensional gas chromatography – high-resolution time-of-flight mass spectrometry (GC×GC-HRTOFMS) for volatile organic compound analysis in the forensic sciences. High-resolution mass spectral data provided higher confidence in analyte identification. GC×GC-HRTOFMS will be valuable for future studies of decomposition odour and other complex volatile matrices.